DNA repair fidelity of base excision repair pathways in human cell extracts. - Zhang, Q; Dianov, G (2005)
Base excision repair (BER), responsible for the removal of altered DNA bases, is accomplished via two pathways that involve different subsets of repair enzymes and result in removal and replacement of one (short-patch BER) or several (long-patch BER) nucleotides. In this study, we constructed single-lesion containing DNA substrates that are predominantly repaired via one of the two pathways and investigated the fidelity of pathway specific repair in human whole cell extracts. We find that a single nucleotide deletion generated during addition of the first nucleotide into the repair gap is the major mutation characteristic for both pathways. This data suggest that for both BER pathways, mutations generated during repair in human whole cell extracts are principally the result of a slippage of DNA polymerase during initiation of repair synthesis.